Estimation of genetic parameters and genotype effects for crossing constructions of Hungarian Pigs - Nagyné Kiszlinger, Henrietta; Molnár, Marcell; Nagy, István (Acta Agraria Debreceniensis, 2013)
Authors estimated the genetic parameters and genotype effects of average daily gain (ADG), age (AGE) and lean meat percentage (LMP) using the field test data of Pietrain (Pi), Duroc (Du), Hampshire (Ha) pigs and their crosses. Data was collected by the Agricultural Agency of Administration between 1998 and 2010 originating from 68 herds. Datasets of the different crossing combinations (Pi, Du, Pi × Du; Pi, Ha Pi × Ha) were evaluated separately using bivariate animal models. The estimated heritabilities were moderately low: 0.24–0.29, 0.22–0.26 and 0.18–0.19 for average daily gain (ADG), age (AGE) and lean meat percentage (LMP), respectively. The estimated genetic correlation coefficients were negligible: -0.07–0.01 (ADG-LMP), -0.01–0.04 (AGE-LMP). The Pi × Ha and Pi × Du crosses showed 6.76% and 4.96%; 6.74% and 4,17% and 0.08% and 0.44% heterosis for ADG, AGE and LMP, respectively. Among the environmental factors the herd effects were substantial: 41.17%, 53.67% and 14.16% for AGD, AGE and LMP, respectively. The smallest environmental influences were found for LMP.